It's all in your head [industrial property]. - Goldstein, H.
In this paper, the author details how understanding your intellectual property rights could help you protect your ideas and save you a lifetime of legal hassles
Keywords: Idea protection; Industrial property; Innovation protection; Intellectual property rights; Legal issues